STUDY OF THE WORKABILITY AND MECHANICAL STRENGTH OF CONCRETE IN THE FACE OF UPWELLING (CASE OF THE EL OUED REGION OF ALGERIA) - Djedid, T; Guettala, A; Mani, M (university of el oued/جامعة الوادي, 2019)
The objective of this study is to explore the effect of partial and total substitution of river sand by crushing sand in ordinary concrete. Various mixtures were tested to evaluate the properties of fresh and hardened concrete exposed to the water rising from the water table. The river sand was substituted by the limestone sand for the following proportions (0%, 30%, 40%, 50%, 60%, 70%, and 100%). The results showed that, the presence of limestone sand greatly improves the properties of strengh and workability. It was noted that these properties were much higher in the presence of crushed limestone sand compared to silica sand in the concrete.The optimal percentage of river sand substitution by crushed limestone sand is 50%.
Article
Keywords: River Sand, Crushed Limestone Sand, Mechanical Strength, Workability, rising water.